Evaluating the Effects of Simulated Golf Cart Traffic on Dormant Buffalograss and Turfgrass Colorants - E. Alderman; J. Hoyle; J. Fry; S. Keeley (Kansas Agricultural Experiment Station Research Reports, 2016)
Percent green cover will ultimately decrease over time when traffic is applied to dormant buffalograss with turfgrass colorants. Data suggests that an additional five weeks of acceptable green cover can be achieved under high traffic situations when Endurant Premium is applied to dormant turf.
Keywords: traffic; Buffalograss; turfgrass